Nepalima Milit Kriya - Gautam, Devi Prasad (Tribhuvan University Journal, 2011)
Not available. Key words: Samyukta kriya; Milit kriya; Yojika; Aadhrit Kriya Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 129-140 Uploaded date: 29 April, 2011